A Simple and Quick Method for the Determination of Pesticides in Environmental Water by HF-LPME-GC/MS - Helvécio C. Menezes; Breno P. Paulo; Maria José N. Paiva; Zenilda L. Cardeal (Journal of Analytical Methods in Chemistry)
This paper describes a simple and quick method for sampling and also for carrying out the preconcentration of pesticides in environmental water matrices using two-phased hollow fiber liquid phase microextraction (HF-LPME). Factors such as extraction mode, time, solvents, agitation, and salt addition were investigated in order to validate the LPME method. The following conditions were selected: 6 cm of polypropylene hollow fiber, ethyl octanoate as an acceptor phase, and extraction during 30 min under stirring at 200 rpm. The optimized method showed good linearity in the range of 0.14 to 200.00 μg L−1; the determination coefficient (R2) was in the range of 0.9807–0.9990. The LOD ranged from 0.04 μg L−1 to 0.44 μg L−1, and LOQ ranged from 0.14 μg L−1 to 1.69 μg L−1. The recovery ranged from 85.17% to 114.73%. The method was applied to the analyses of pesticides in three environmental water samples (a spring and few streams) collected in a rural area from the state of Minas Gerais, Brazil.